Chitosan beads from microbial and animal sources as enzyme supports for wine application. (December 2016) - Benucci, Ilaria; Lombardelli, Claudio; Cacciotti, Ilaria; Liburdi, Katia; Nanni, Francesca; Esti, Marco
Abstract: Chitosan beads from a microbial source, i.e. Aspergillus niger (An), were produced by precipitation method for the first time and compared with supports prepared from an animal source, i.e. shellfish derived chitosan with three different molecular weights (low (LMW), medium (MMW) and high (HMW)). The produced beads were used as enzyme carriers to be applied in a continuous packed-bed reactor (PBR) for white wine protein stabilization. For this purpose, the beads were crosslinked with glutaraldehyde (GDH) and stem bromelain was immobilized on the carrier surface as a model enzyme, following two different procedures (i.e., crosslinking with glutaraldehyde (GDH) and direct linkage (DL)). Drop-like beads with an average diameter of 3.0–3.5 mm and a moisture content of 86–94% were obtained. The morphology of the produced beads in dried state, in terms of shape and surface, was studied by means of a scanning electron microscope (SEM), evidencing the obtainment of nearly spherical or oval particles. The efficacy of the crosslinking procedure and of bromelain immobilization was demonstrated by means of SEM investigation and infrared spectroscopy (FT-IR) analysis, revealing a rougher surface. Various initial protein concentrations ranging between 0.45 and 18.00 mgBSAeq mL −1 were tested in order to identify the optimal amount and to evaluate the influence of the initial concentration on the total protein loading. Stem bromelain proved to be more active when immobilized by DL on An beads and was efficient in reducing white wine hazing potential continuously, as verified with a laboratory bench-scale PBR. Graphical abstract: Highlights: Microbial chitosan beads were obtained for the first time as enzyme carriers. Bromelain was immobilized on chitosan beads by GDH crosslinking or direct linkage. The efficacy of crosslinking and immobilization was proved by SEM, DSC and FT-IR. Bromelain was more active when immobilized by direct linkage on microbial chitosan. Bromelain on microbial chitosan was useful for white wine stabilization in PBR.